Discrete Time Homogeneous Markov Processes for the Study of the Basic Risk Processes - D’Amico, Guglielmo; Gismondi, Fulvio; Janssen, Jacques; Manca, Raimondo (Methodology and computing in applied probability, 2015)
In this paper Markov models useful for following the time evolution of the aggregate claim amount and the claim number in the homogeneous time environment are presented. More precisely the homogeneous Markov reward processes in both discounted and not discounted cases are applied to solve the aggregate claim amount and the claim number processes respectively. In the last section the application of the proposed models is presented. Two different real-world databases are mixed for the construction of input data.